Slow Freezing or Vitrification of Oocytes: Their Effects on Survival and Meiotic Spindles, and the Time Schedule for Clinical Practice - Shee-Uan Chen; Yu-Shih Yang (Taiwanese Journal of Obstetrics & Gynecology, 2009)
Both the slow-freezing method with increased sucrose concentration and new vitrification techniques significantly improve the results of cryopreservation of human oocytes. The recent perfection for vitrification includes the concepts of increase of cooling and warming rates using minimum volume methods, and decrease of toxicity by reducing the concentration of cryoprotectants. In the recent literature, the survival of cryopreserved oocytes ranged from 74% to 90% using the slow-freezing method and from 84% to 99% by vitrification. Overall, the survival rate of oocytes from vitrification (95%, 899/948) appeared higher than that of the slow-freezing method (75%, 1,275/1,683). The microtubules of meiotic spindles are vulnerable to the thermal changes and will depolymerize. After incubation, the microtubules repolymerize. Spindle recovery is faster after vitrification than slow freezing. Even so, after 3 hours of incubation, spindle recuperation is similar between vitrification and slow freezing. Considering both aspects of spindle recovery and oocyte aging, the time schedule for oocyte cryopreservation program makes fertilization in the optimal time. Intracytoplasmic sperm injection is performed for oocytes at 3 hours of post-thaw incubation from the slow-freezing method and 2 hours from vitrification, with restoration of meiotic spindles. The pregnancy potential of cryopreserved oocytes is comparable to that of fresh oocytes or frozen embryos. Cryopreservation of oocytes would importantly contribute to oocyte donation and preservation of fertility for cancer patients.